Konflik Tokoh Utama Dalam Cerkak ‘Pasa Ing Paran‘ Karya Impian Nopitasari (DIWANGKARA: Jurnal Pendidikan Bahasa, Sastra dan Budaya Jawa, 2022)
This study aims to gain an understanding of the external and internal conflict of the main character in the short story Pasa Ing Paran by Impian Nopitasari. The method used in this research is descriptive qualitative. The data in this study are literary texts that cover internal and external conflicts based on the Linda L. Davidoff theory. The data are taken from a short story entitled Pasa Ing Paran. The data collection technique is a documentary study technique by examining literary works as a source of research data. Based on data analysis, the short story Pasa Ing Paran represents internal and external conflicts experienced by the main character named Puguh. The results show that there are internal conflicts experienced by Puguh in the form of regret, indecision, and the emergence of feelings of inadequacy. In addition, external conflicts are also experienced by Puguh, such as the impact of the corona virus, fights between Puguh and road border guards, and fights between Puguh and the community. This research is expected to be a reference for the development of future research that intends to examine the internal and external conflicts in literary works.
Keywords: Conflict; Main Character; Short Story